A comparison of rectal palpation and ultrasonography for the detection of follicle(s) and corpus luteum in pluriparous buffaloes - HONPARKHE, M; GANDOTRA, V K; NANDA, A S; PRABHAKAR, S (The Indian Journal of Animal Reproduction, 2023)
~ix normal cycling pluriparous buffaloes were examined by palpation per rectum and by ultrasonography to find thecomparative detectability of follicle and corpus luteum (CL) during different stages of estrous cycle. The ovaries of thesebuffaloes were palpated and scanned at estrus (day 0), metestrus (day 2), mid-diestrus (day 9) and late-diestrus (day 16). Thefollicles were palpated in four (66.67 %) out of six buffaloes at estrus by per rectal palpation and in all the six (1000/o) byultrasonography. The mean size of follicle at estrus detected by ultrasonography was 1.08 ± 0.21 cm. The CL on days 2, 9 and16 was detected by ultrasound in all the buffaloes (100%) and in three (50 %), six (100%) and one (16.67%) buffaloes bypalpation per rectum, respectively. The mean size of CL as measured by ultrasound was 0.89 ± 0.09, 1.17 ± 0.17 and 0.80 ±0.07 cm on day 2, 9 and 16, respectively. The identification and measurement of follicles and CL were easier by ultrasonographythan by palpation as follicles and CL measuring less than 0.90 cm were not detected by palpation most of the times.
Keywords: Ultrasonography; corpus luteum; follicle; estrous cycle